Optimization of Silicon solar cell in MATLAB/SIMULINK for improved efficiency - Panchal, Rutvi Rohit; Jolly, Lochan (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Solar energy is an important part of life and has been in use since the beginning of time. Increasingly, man is learning how to yoke this important resource and use it to replace traditional energy sources. Solar cells are the development to store the solar energy and reproduce electricity. But the amount of energy converted is very less, that is the efficiency of conversion is poor. The main challenge is to improve the efficiency so that the losses can be minimized. The Maximum Power Points are found and the Fill Factor is calculated. Â The comparative study of silicon solar cell and panels with different sizes is done in this paper using MATLAB and SIMULINK model. The simulated results are compared with practically tested solar cell at Standard Test Conditions (STC).